2022
DOI: 10.32604/cmc.2022.024604
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Computational Methods for the Polio Virus Epidemic Model

Abstract: In 2021, most of the developing countries are fighting polio, and parents are concerned with the disabling of their children. Poliovirus transmits from person to person, which can infect the spinal cord, and paralyzes the parts of the body within a matter of hours. According to the World Health Organization (WHO), 18 million currently healthy people could have been paralyzed by the virus during 1988-2020. Almost all countries but Pakistan, Afghanistan, and a few more have been declared polio-free. The mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Our review identified nine other studies that presented DEB models of poliovirus transmission for theoretical populations using different numerical simulation methods [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review identified nine other studies that presented DEB models of poliovirus transmission for theoretical populations using different numerical simulation methods [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…The bottom portion of Table 2 shows the geographic scope covered by 45 studies that included poliovirus transmission modeling [ 7 , 9 , 10 , 11 , 12 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 25 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 67 , 79 , 80 , 81 , 87 , 88 , 89 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Not surprisingly, two groups published studies on Pakistan, Afghanistan and Nigeria, which continue to represent critical geographies for polio eradication.…”
Section: Resultsmentioning
confidence: 99%